Respuesta :

Answer:

-15

Step-by-step explanation:

start from the inside and go out.

So first plug in -3 into g(x)

g(-3) = -3 - 7 = -10

then plug in -10 into f(x)

f(-10) = 2(-10) + 5 = -15

so f(g(x)) = -15

Answer:

The answer is - 15

Step-by-step explanation:

f(x) = 2x + 5

g(x) = x − 7

To find f(g(x)) substitute g(x) into f(x) that's replace every x in f(x) by g(x)

That's

f(g(x)) = 2(x - 7) + 5

= 2x - 14 + 5

f(g(x)) = 2x - 9

When x = - 3

Substitute - 3 into f(g(x))

That's

f(g(3)) = 2(-3) - 9 = - 6 - 9 = - 15

Hope this helps you